Numerical Simulation of n‐MoSe2/p‐Si Solar Cells by AFORS‐HET. Issue 7 (10th April 2022) - Shen, Yuheng; Yu, Meng; Huang, Ruiming; Cheng, Qijin
Abstract: For a thorough understanding of n‐MoSe2 /p‐Si heterojunction solar cells, the effect of the MoSe2 band gap, the back electrode work function, the density of interface states, as well as the introduction of the interface layer on the performance of MoSe2 /Si heterojunction solar cells is systematically investigated via AFORS‐HET simulation software. It is shown that a higher MoSe2 band gap, a higher back electrode work function, a lower density of interface states, and an introduction of a thin intrinsic hydrogenated amorphous silicon as an interface layer, are favorable for the achievement of high‐performance MoSe2 /Si heterojunction solar cells. Through the simulation optimization, a photovoltaic conversion efficiency of 12.31% with an open‐circuit voltage of 0.61 V, a short‐circuit current density of 26.47 mA cm −2, as well as a fill factor of 75.4%, can be obtained for the n‐MoSe2 /p‐Si heterojunction solar cells. To interpret the obtained simulation results, the authors have carefully analyzed the current–voltage curves, energy band diagrams, electron and hole concentration distributions, electron and hole recombination rates, etc. This study indicates that silicon‐based heterojunction solar cells with MoSe2 as an active layer are of great significance in the development of high‐efficiency photovoltaic devices. Abstract : AFORS‐HET is employed to investigate the effect of various parameters on the performance of MoSe2 /Si heterojunction solar cells. It is shown that a higher MoSe2 band gap, a higher back electrode work function, a lower density of interface states, and an introduction of a thin a ‐Si:H( i ) as an interface layer, are favorable for the achievement of high‐performance solar cells.